Series of Discrimination: Exploring Discrimination among Children - Patricia Tanjung (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
This series of children’s literature focuses on discrimination among children based on their race, sex, disability, physical attractiveness, and social class. The goal is to find the ways children discriminate against their friends and also the ways they cope with discrimination. To do so, this creative thesis uses the concept of prejudice and discrimination and also the theory of Coping. From the series, it is shown that children can verbally, behaviorally, and relationally discriminate against their friends and that children can use problem-focused coping to cope with discrimination. Therefore, by understanding ways discrimination manifests itself and knowing how to cope with discrimination, children can detect discrimination and learn to cope with it.Keywords: Discrimination, Picture Books, Children’s literature, Realistic fiction